PERAN IKLAN DAN BRAND AWARENESS TERHADAP NIAT BELI PENGGUNA TOKOPEDIA PADA PASCA COVID-19 - Setiari, Dewa Ayu Shita; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 11 No 8 (2022)DO - 10.24843/EJMUNUD.2022.v11.i08.p06, 2022)
Consumer needs in the advancement of the digitalization era by utilizing a marketplace that is quite attractive and provides convenience, especially during the post-covid-19 era. This study aims to examine the role of brand awareness in mediating the effect of advertising on purchase intention. The sample was taken by 100 respondents who live in the city of Denpasar, people who have never shopped online at Tokopedia. The analysis technique used is path analysis and using Sobel test. Research findings show, advertising and brand awareness have a positive and significant effect on purchase intention, and brand awareness is able to act as a mediator of the relationship between the influence of advertising on purchase intention at Tokopedia. Subsequent implementation is very important to innovate the advertisements displayed so as to strengthen brand awareness that is able to encourage purchase intention in a sustainable manner. Keywords: , advertising, brand awareness, purchase intention